Unions, dynamism, and economic performance - Barry T. Hirsch (Institute for the Study of Labor (IZA), 2010)
This paper explores the relationship between economic performance and US unionism, focusing first on what we do and do not know based on empirical research handicapped by limited data on establishment and firm level collective bargaining coverage. Evidence on the relationship of unions with wages, productivity, profitability, investment, debt, employment growth, and business failures are all relevant in assessing the future of unions and public policy with respect to unions. A reasonably coherent story emerges from the empirical literature, albeit one that rests heavily on evidence that is dated and (arguably) unable to identify truly causal effects. The paper's principal thesis is that union decline has been tied fundamentally to competitive forces and economic dynamism. Implications of these findings for labor law policy and the future of worker voice institutions is discussed briefly in a final section.
Keywords: J50; J20; J30; 330; unions; economic performance; competition; dynamism